ANALISIS RESEPSI PENONTON PEREMPUAN TENTANG PERILAKU GASLIGHTING DALAM WEB SERIES YANG HILANG DALAM CINTA PADA DISNEY+ HOTSTAR - Gusti Illahi, Abdhi; Zamzamy, Ahmad (Linimasa : Jurnal Ilmu Komunikasi, 2025)
Abstract The purpose of this research is to analyze the reception of female viewers towards gaslighting behavior in the web series "Yang Hilang Dalam Cinta" on Disney+ Hotstar. This study employs Stuart Hall's reception theory, which categorizes audiences into three groups in interpreting media messages: Dominant-Hegemonic Code, Negotiated Code, and Oppositional Code. This research uses a descriptive qualitative method by describing the research results using Stuart Hall's reception theory. In determining the informants, this research uses purposive sampling technique with the criteria of being female, currently or previously in a romantic relationship, and having watched the web series "Yang Hilang Dalam Cinta" on Disney+ Hotstar. From in-depth interviews with eight informants, six informants are in the dominant position, and two informants are in the negotiation position. Informants in the dominant position agree with the message of the series, concurring that gaslighting is a wrong and harmful behavior because it can make women powerless in a romantic relationship and lead to a range of negative impacts. Meanwhile, informants in the negotiation position also acknowledge that gaslighting is a harmful behavior, but they consider the educational aspect of the series. According to them, the presence of this series can provide examples of gaslighting behavior and its negative impacts so that women out there can have better awareness. Keyword: Gaslighting, Web Series, Women, Reception Analysis Stuart-Hall